2012
DOI: 10.1128/aac.05885-11
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Farnesol Contributes to Increased Susceptibility to β-Lactams in Strains of Burkholderia pseudomallei

Abstract: cThis study aimed to evaluate the in vitro combination of farnesol and ␤-lactams against Burkholderia pseudomallei. A total of 12 ␤-lactamase-positive strains were tested according to CLSI standards. All strains were inhibited by farnesol, with MICs ranging from 75 to 150 M. The combination of this compound with ␤-lactams resulted in statistically significant ␤-lactam MIC reduction (P < 0.05). This study provides new perspectives for the use of farnesol combined with ␤-lactam antibiotics against strains of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…Several studies have confirmed the inhibitory effect of farnesol on the growth of several bacteria (12,13,27). More recently, many studies have described the activity of farnesol against different species of fungi (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have confirmed the inhibitory effect of farnesol on the growth of several bacteria (12,13,27). More recently, many studies have described the activity of farnesol against different species of fungi (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 97%
“…Brilhante et al showed that farnesol had an inhibiting activity alone and in combination with antifungal agents against strains of dimorphic fungi from the genus Coccidioides and against Candida spp. clinical isolates [4,5]. Nerolidol shows a toxic effect against, inter alia, Salmonella enterica, Staphylococcus aureus, Escherichia coli and Aspergillus niger, and increases the antibacterial activity of antibiotics [6,7].…”
Section: Figurementioning
confidence: 99%
“…Farnesol, which is present in many creams and nourishing agents, has a bacteriostatic effect against bacteria that can cause acne (Staphylococcus aureus, Staphylococcus epidermidis) and does not affect naturally occurring microflora on the skin [1]. It blocks the formation of biofilm by the drug-resistant strains of Staphylococcus aureus and acts synergistically with antibiotics [2][3][4]. Brilhante et al showed that farnesol had an inhibiting activity alone and in combination with antifungal agents against strains of dimorphic fungi from the genus Coccidioides and against Candida spp.…”
Section: Figurementioning
confidence: 99%
“…Many studies have sought new compounds with antimicrobial activity. The sesquiterpene farnesol has gained prominence due to its high antimicrobial activity against bacteria and fungi (Inoue et al, 2004;Jabra-Rizk et al, 2006;Brilhante et al, 2012Brilhante et al, , 2013. Its potential antifungal activity has already been demonstrated against different species of Candida and Cryptococcus , as well as against Coccidioides posadasii and Paracoccidioides brasiliensis (Derengowski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%